Analisis SWOT PT. ASDP Indonesia Ferry (Persero) Pelabuhan Ketapang-Gilimanuk - Erlina Lestari; Kadek Rai Suwena (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
The’’’’purpose…of**this study is to analyze the strengths (strengths), weaknesses (weaknesses), opportunities (opportunities) and threats (Threats) using a SWOT analysis on the quality of services of PT. ASDP Indonesia ferry (persero) Ketapang-Gilimanuk port. This study uses this type…of…research with descriptive research methods that describe the quality of services PT. ASDP Indonesia Ferry (Persero) Ketapang-Gilimanuk Port. The population in this study are service users who use the services of PT. ASDP with the sample used as many as 384 respondents obtained using accidental sampling technique. Data were collected by observation, questionnaires and documentation and analyzed using quantitative descriptive analysis. The results obtained from compiling a SWOT matrix analysis based on IFAS, namely the total score of the strength factor minus the total score of the weakness factors of the service quality of PT. ASDP Ketapang-Gilimanuk Port obtained 1.5 results. Meanwhile, based on EFAS, the opportunity score is reduced by the threat factor score, the result is 2.25.